2017
DOI: 10.4103/ijo.ijo_217_17
|View full text |Cite|
|
Sign up to set email alerts
|

Allergen-specific exposure associated with high immunoglobulin E and eye rubbing predisposes to progression of keratoconus

Abstract: We report two male children with persistent allergic eye disease (AED) and keratoconus (KC). Both presented with symptoms of vernal keratoconjunctivitis and decreased vision. In view of unrelenting AED, serum immunoglobulin E (IgE) quantification and identification of specific allergens were advised. Increased serum IgE levels were observed in both cases. Sunflower and sheep wool were identified as specific allergens for the first and second patient respectively by skin patch test. There was complete resolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 13 publications
(17 reference statements)
1
14
0
Order By: Relevance
“…A significant correlation between KC progression with hormonal changes, as in pregnancy, lactation and thyroid eye disease,3,4 was elucidated in the literature 5. Vernal keratoconjunctivitis (VKC), chronic eye rubbing, dry eye disease and limbal stem cell inefficacy have been reported as aggressive factors that both promote KC progression and treatment failure especially in pediatric patients 6,7…”
Section: Introductionmentioning
confidence: 99%
“…A significant correlation between KC progression with hormonal changes, as in pregnancy, lactation and thyroid eye disease,3,4 was elucidated in the literature 5. Vernal keratoconjunctivitis (VKC), chronic eye rubbing, dry eye disease and limbal stem cell inefficacy have been reported as aggressive factors that both promote KC progression and treatment failure especially in pediatric patients 6,7…”
Section: Introductionmentioning
confidence: 99%
“…Nonsurgical management of KC should include verbal guidance to avoid eye rubbing, use of topical anti-allergic medication in patients with allergy, and use of lubricants for ocular irritation [ 3 ]. In early cases, control of the allergic reaction to decrease the eye rubbing impulse may reduce the inflammation and help avoid corneal complications [ 28 ]. Salomao et al [ 29 ] stress the need for screening; though moderate and advanced cases of keratoconus are easily recognized, identification of mild and early forms of keratoconus remains a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…[9–11] However, some investigations have indicated that the eye rubbing itself may play a crucial role in the development of corneal ectasia in keratoconus. [6,7,11,12] Accidental or self-induced ocular injuries may also cause keratoconus, with 3 reports demonstrating an association between keratoconus and TS. [1315]…”
Section: Introductionmentioning
confidence: 99%